BIOSYNTHESIS AND CHARACTERIZATION OF MAGNESIUM OXIDE DOPED WITH POLYINDOLE AND ITS WOUND HEALING PROPERTIES - Arsha A,; Jeena Pearl A, (The Bioscan, 2025)
Magnesium oxide is recognized for its antimicrobial characteristics, stability, and biocompatibility, rendering it a significant material for biomedical applications. MgO was amalgamated with polyindole, a conductive polymer, to create a composite with augmented biological activity. The composite's structural and morphological characteristics were analyzed using FT-IR, XRD, SEM, and EDAX to verify its composition and crystallinity. The Magnesium oxide doped polyindole composite demonstrated significant antibacterial efficacy, essential for infection prevention in wound healing. Furthermore, it stimulated fibroblast proliferation and expedited wound healing, indicating its promise in tissue regeneration. The integration of polyindole enhanced the material's conductivity and its interaction with biological systems, hence enhancing its efficacy. The findings indicate that the Magnesium oxide doped Polyindole composite is a viable material for wound healing and regenerative medicine, providing both antimicrobial protection and improved biocompatibility.